Networked library access and services delivery for the blind and visually impaired university students: evidence from the UAE. Issue 3 (19th August 2019) - Al-Harrasi, Alia; Taha, Ahmed
Abstract : Purpose: The study aims to discuss the special needs-centric information delivery as a new genre of the academic library services. It also sheds light on the assistive technology used to help blind or visually impaired (BVI) students to access the available digital contents and use online services conveniently. A particular emphasis placed on gaining some insights into BVIs' perceptions towards the orientation and assistance offered by the access service librarians, as well as any experience in using assistive educational technology for reading and information access. Design/methodology/approach: The authors used semi-structured interview survey to gather the necessary data from 35 BVI university students drawn from the Special Needs Services (SNS) Unit at the UAE University. The interview was concerned with use of library e-resources and online services for doing their assignments, easy-to-use facilities to access the e-resources and main challenges facing them in communicating with the librarians. Findings: The findings revealed that the BVI students considered that the university library does not answer their needs for getting access to digital content and using online services adequately. Practical implications: The Main Library should cooperate closely with the SNS Unit to get the most benefits from their experience in the BVI-devoted services to develop an efficient library information discovery and delivery to this student group. Originality/value: There is scarcity of scholarly studies on the pedagogical and information acquisition challenges facing the BVI university students in the UAE higher education. This is the first research study that tackles the experience of the BVI students in using the academic library.